Investigation of Eating Habits in Patients with Functional Dyspepsia - Çolak, Hatice; Güneş, Fatma Esra; Özen Alahdab, Yeşim; Karakoyun, Berna (Turkish Journal of Gastroenterology, 2022)
Background: Nutritional habits of patients with functional dyspepsia can affect the progression of functional dyspepsia. We aimed to determine the foods and dietary habits that may cause symptoms of postprandial fullness, early satiety, epigastric pain, and epigastric burning in functional dyspepsia patients. Methods: Sixty functional dyspepsia patients, who were diagnosed according to Rome IV criteria in the endoscopy unit of a gastroenterology institute, were included in the study. Data on the demographic characteristics, anthropometric measurements, nutritional habits, and food consumption frequency questionnaire of functional dyspepsia patients were collected. Results: Postprandial fullness was found more common in those who preferred roasting as a cooking method. There was no significant difference between symptoms and meal frequency. Epigastric burning and pain were found to be more pronounced in women, and alcohol consumption was less in patients who experienced more epigastric pain. In non-smoker participants, the complaint of early satiety was lower. It was found that broccoli, radish, celery, green olives, and olive oil consumption was less in participants who experienced excessive postprandial fullness. Patients with stomach pain consumed less dry fruits, green olives, butter, alcohol, and fast food. It was found that patients with stomach burning consumed less alcohol and fast food. Conclusion: In conclusion, functional dyspepsia patients should avoid or reduce consuming broccoli, radish, celery, green olives, olive oil, dry fruits, and butter which may trigger symptoms. Reducing consumption of these foods, abandoning unhealthy cooking methods such as roasting, reducing smoking, and reducing consumption of alcohol and fast food might be beneficial for relieving symptoms. Cite this article as: Çolak H, Güneş FE, Özen Alahdab Y, Karakoyun B. Investigation of eating habits in patients with functional dyspepsia. Turk J Gastroenterol. 2022;33(8):673-681.